Rehabilitation in chronic kidney disease patients on hemodialysis: A systematic literature review (Research, Society and Development, 2022)
Introduction: Chronic Kidney Disease (CKD) represents a slow, progressive and irreversible loss of kidney function. Treatment may range from conservative to substitutive therapies such as hemodialysis. As a result, patients undergoing treatment may present secondary changes to hemodialysis that could be treated and prevented by physical therapy interventions through physical exercises applied in the intradialytic period. Objective: To analyze the effects of physiotherapeutic rehabilitation when applied in patients with CKD during hemodialysis sessions. Methods: This is a systematic literature review, which concentrated clinical trials found in the databases: LILACS, PEDro and PubMed, published in Portuguese and English languages, between 2016 and 2021, which were subsequently standardized according to the PEDro Scale. Results: Of the 229 articles found, 21 clinical trials were analyzed. In general, interventions such as aerobic exercise, resistance exercise, combined exercise, thermotherapy and respiratory muscle training were presented. Furthermore, it was possible to observe improvement in muscle strength, functional capacity, exercise capacity, physical inactivity, cardiovascular risk factors, and improvement in sleep quality, besides providing improvement in aspects related to inflammatory biomarkers and quality of dialysis. These exercises were performed with an average of 30 to 40 minutes, three times a week, for an average of 12 weeks. Conclusion: It can be concluded that an intradialytic rehabilitation program can offer positive effects to the patient on hemodialysis. However it is suggested that the quality of life of these patients should be treated as a primary outcome, getting this way a complete and wide rehabilitation of patients with CKD.